Low-loaded Platinum electrocatalysts on non-carbon supports for the development of direct ethanol fuel cells - Modise, Refiloe Petronella (My University, 2020)
Platinum-based electrocatalysts (Pt/TiO2, Pt/TiO2Mn, Pt/TiO2Ce, Pt/TiO2Mn0.5Ce0.5 and Pt/TiO2Ce/C) were prepared using the alcohol reduction method. The electrocatalysts were characterized using X-ray diffraction (XRD), Raman spectroscopy, ultraviolet-visible spectroscopy (UV-vis.), Scanning electron microscopy (SEM), transmission electron microscopy (TEM) and X-ray photoelectron spectroscopy (XPS) to investigate their physical properties. This was followed by the electrochemical behaviour evaluation in ferri-ferrocyanide (Fe(CN)63-/Fe(CN)64-) using cyclic and linear sweep voltammetry, chronoamperometry (CA) electrochemical impedance spectroscopy (EIS) and Bode impedance. A fast electron (e-) transfer and enhanced Faradaic current was exhibited by Pt/TiO2Ce/C relative to the other electrocatalysts, aided by the electronic conductivity of carbon. This was illustrated by the smaller peak potential separation, large active area and high electrode surface coverage compared to the other electrocatalysts. The electrocatalysts illustrated a mixed adsorption-diffusion controlled (more of diffusion) mass transport mechanism as demonstrated by the effect of scan rate on the peak current. Thereafter, the electrochemical behaviour of the electrocatalysts towards ethanol oxidation reaction (EOR) was evaluated in acidic and alkaline electrolyte separately using cyclic voltammetry (CV), linear sweep voltammetry (LSV), CA and EIS techniques. The results illustrated the dependence of EOR on the co-catalysts manganese (Mn) and/or manganese oxide (MnOX) as well as cerium (Ce) and/or ceria (CeOx) in titanium dioxide (TiO2). Especially, the catalysts supported on TiO2/Ce and/or CeOx which exhibited lower onset potential (Eonset), fast electron transport (smaller ΔEp), enhanced Faradaic current response, high exchange current densities and lower charge transfer resistance (Rct). The activity towards the EOR was observed to increase in the following order: Pt/TiO2 < Pt/TiO2Mn < Pt/TiO2Mn0.5Ce ≤ Pt/TiO2Ce < Pt/TiO2Ce/C. Moreover, the electrocatalysts, Pt/TiO2, Pt/TiO2Mn, Pt/TiO2Ce, Pt/TiO2Mn0.5Ce0.5 and Pt/TiO2Ce/C were investigated for their electrochemical behaviour towards oxygen reduction reaction (ORR). Again, Pt/TiO2Ce exhibited enhanced activities showing more positive Eonset and half-wave potential (E1/2) accompanied by high diffusion-limited current density (jd). However, it was interesting to note that the Pt/TiO2Mn was more efficient towards ORR, indicated by the number of electrons (n) determined from the Koutecky-Levich (K-L) plots and equation. According to the K-L plots, the ORR for the Pt/TiO2, Pt/TiO2Mn, Pt/TiO2Mn0.5Ce0.5, Pt/TiO2Ce/C proceed via the 4 e- and Pt/TiO2Ce demonstrated a 2 e- processes. The catalytic activity towards ORR increased in the following order: Pt/TiO2Mn < Pt/TiO2 < Pt/TiO2Mn0.5Ce0.5 < Pt/TiO2Ce < Pt/TiO2Ce/C
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science, 2020